1970
DOI: 10.1111/j.2042-7158.1970.tb08447.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of ethanol and amphetamine metabolism

Abstract: Ethanol, 1,3, and 5 g/kg, depresses the hydroxylation of amphetamine by the rat in vivo. At 5 g/kg, ethanol does not affect the hydroxylation of acetanilide or biphenyl in vivo. Amphetamine hydroxylation is unaffected by phenobarbitone or benzo[a]pyrene pretreatment but is depressed by pretreatment with 2-diethylaminoethyl-2,2-diphenylvalerate (SKF 525-A), 2,4-dichloro-6-phenylphenoxyethylamine (DPEA), and 2,4-dichloro-6-phenylphen~xy-NN-dieth~leth~lamine (Lilly 18947).We have reported previously that ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…1,3-DiMeTIQ may be formed by ring cyclization of amphetamines, analogs of phenylethylamine, with acetaldehyde, an oxidized product of ethanol. It is reported that ethanol treatment markedly inhibits the phydroxylation of amphetamine and induces a higher level of amphetamine in rat brain and blood (Creaven and Barbee, 1969;Creaven et al, 1970;Todzy et al, 1978;Shimosato, 1988). The effect of ethanol may cause ring cyclization of amphetamine more readily in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…1,3-DiMeTIQ may be formed by ring cyclization of amphetamines, analogs of phenylethylamine, with acetaldehyde, an oxidized product of ethanol. It is reported that ethanol treatment markedly inhibits the phydroxylation of amphetamine and induces a higher level of amphetamine in rat brain and blood (Creaven and Barbee, 1969;Creaven et al, 1970;Todzy et al, 1978;Shimosato, 1988). The effect of ethanol may cause ring cyclization of amphetamine more readily in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In the numerous studies Concerned with the aspect of metabolic interaction, mostly an inhibitory effect of ethanol on the metabolism of drugs in vivo (SCHUPPEL 1969;CREAVEN et al 1970;THOMAS et al 1972) and in vitro (SCHUPPEL et ul. 1967;RUBIN et al 1970a;PETRUCH & SCHUPPEL 1971) as well as on the metabolism of other foreign compounds (VILLENEUVE & PHIL-LIPS 1971; COHEN & MNERING 1973) has been observed and has been ascribed to a direct inhibitory action of ethanol on the microsomal mixed function oxidation pathway (SCHUPPEL 1969).…”
mentioning
confidence: 99%